Themes and trends in marathon performance research: a comprehensive bibliometric analysis from 2009 to 2023 (Frontiers in Physiology, 2024)
Background When marathon runners break the 2-h barrier at the finishing line, it attracts global attention. This study is aimed to conduct a bibliometric analysis of publications in the field of marathon running, analyze relevant research contributors, and visualize the historical trends of marathon performance research over the past 15 years.